The Effect of Application-Based Exergames on Cognitive Function in Hemodialysis Patients - Fauzi, Achmad; Lindayani, Linlin; Mutiar, Astri; Darmawati, Irma (STIKep PPNI Jawa Barat, 2024)
Aims: Hemodialysis (HD) patients may disrupt physical and cognitive capabilities, affecting older mobility, independence, psychological well-being, and health care expenditures. Home-based exergame training overcomes accessibility issues. Methods: This research examined how mobile app exergames affected cognitive performance in hemodialysis patients. This research used a repeated measurement-quasi-experiment two-group pretest-posttest design in a West Java. The intervention group trained three times a week for 30-40 minutes for two months, totaling 24 sessions (8 weeks). In the control group, participants were told to live normally. Results: Inlcusion criteria was performing HD at least twice a week, age > 65, living independently, self-reported health, ability to stand for 10 minutes without help, and access to a TV with HDMI connection. The Trail Making Test (TMT) measured psychomotor speed and executive function. ANCOVA was used to compare scores before and after the intervention in both groups. The repeated ANOVA test revealed that the trial making test A (TMT A) decreased significantly in the intervention group after one month intervention (T2) (from 79.77 ± 7.23 at baseline to 40.87 ± 5.33 at follow up), with the effect size was 0.41, indicating moderate effect size. The trial making test B (TMT B) decreased significantly in the intervention group after one month intervention (T2) (from 77.6 ± 24.2 at baseline to 70.32 ± 23.3 at follow up), with the effect size was 0.45, indicating moderate effect size. However, there was not significant change of Trial making Test A and B from baseline to follow up time in the control group. Conclusions: Findings of this study could be one of the new solutions to help patients undergoing hemodialysis improve their cognitive function. Exergame training may be done at home, which helps to overcome accessibility constraints.